The Effects of Antipsychotics on the Brain: What Have We Learnt from Structural Imaging of Schizophrenia? A Systematic Review - Smieskova, R.; Fusar-Poli, P.; Allen, P.; Bendfeldt, K.; Stieglitz, R. D.; Drewe, J.; Radue, E. W.; McGuire, P. K.; Riecher-Rossler, A.; Borgwardt, S. J. (Current Pharmaceutical Design, 2009)
Despite a large number of neuroimaging studies in schizophrenia reporting subtle brain abnormalities, we do not know to what extent such abnormalities reflect the effects of antipsychotic treatment on brain structure. We therefore systematically reviewed cross-sectional and follow-up structural brain imaging studies of patients with schizophrenia treated with antipsychotics. 30 magnetic resonance imaging (MRI) studies were identified, 24 of them being longitudinal and six cross-sectional structural imaging studies. In patients with schizophrenia treated with antipsychotics, reduced gray matter volume was described, particularly in the frontal and temporal lobes. Structural neuroimaging studies indicate that treatment with typical as well as atypical antipsychotics may affect regional gray matter (GM) volume. In particular, typical antipsychotics led to increased gray matter volume of the basal ganglia, while atypical antipsychotics reversed this effect after switching. Atypical antipsychotics, however, seem to have no effect on basal ganglia structure.
Keywords: typical